Strategy of Using Wireless Technology Sophistication for Rural Community Development in Malaysia Abstract - Bohari, Abdul Manaf; Md. Zan, Zainal (Journal of Asian Business Strategy, 2012)
Community developmnent currently is change dramatically with increased the needs of wirelss technology sofistication as a major part of social life. In contact of Malaysia, wireless technology, has been introduced to rural, semi-rural and hidden area areas where there are some questions regarding the wireless sofistication needs and requirement. The questions are (a) what is interest of non-urban people on usage the wireless technology; and (b) what is factor that make them to used wireless technology in their social life. The objective of study is to explore the needs of rural people toward wireless sophistication with focused on wireless specifications and features. The second objective is to explore factors that considers by rural-community regarding their adoption to wireless technology. To conduct this study, un-structured interview were conducted to 40 respondents in selected rural, semi-rural and hidden area of Malaysia-Thailand bourder as well as Sintok, Changlun, Bukit Kayu Hitam, and Bukit Tangga in Kedah. Furthermore, this study will present the clear description of the need of wireless technology that needed by rural society. The finding of study will lead to establish guideline on how to utilize wireless technology for developing the society of rural area in Malaysia, as effectively.